Adsorption Characteristics of Activated Red Mud for Lead Removal - Kong, Chun-Yan (Asian Journal of Chemistry, 2011)
Red mud is the waste of alumina industry and has high Fe2O3 and SiO2 content which are active components for the adsorption of heavy metal anion pollutants. In this study, the uptake of lead by red mud activated by heat treatment was investigated. The factors influencing the adsorption were also investigated. The result showed that the red mud sample treated using heat reatment at 700 ºC for 2 h achieved the highest lead removal. Lead removal by the activated red mud was significantly pH dependent. The adsorption fits Langmuir isotherm model well and the maximum adsorption capacities of the heat activated red mud was 38.2 mg/g.